Hypercapnia modulates cAMP signalling and cystic fibrosis transmembrane conductance regulator‐dependent anion and fluid secretion in airway epithelia. (20th December 2015) - Turner, Mark J.; Saint‐Criq, Vinciane; Patel, Waseema; Ibrahim, Salam H.; Verdon, Bernard; Ward, Christopher; Garnett, James P.; Tarran, Robert; Cann, Martin J.; Gray, Michael A.
Abstract : Key points: Raised arterial blood CO2 (hypercapnia) is a feature of many lung diseases. CO2 has been shown to act as a cell signalling molecule in human cells, notably by influencing the levels of cell signalling second messengers: cAMP and Ca 2+ . Hypercapnia reduced cAMP‐stimulated cystic fibrosis transmembrane conductance regulator‐dependent anion and fluid transport in Calu‐3 cells and primary human airway epithelia but did not affect cAMP‐regulated HCO3 − transport via pendrin or Na + /HCO3 − cotransporters. These results further support the role of CO2 as a cell signalling molecule and suggests CO2 ‐induced reductions in airway anion and fluid transport may impair innate defence mechanisms of the lungs. Abstract: Hypercapnia is clinically defined as an arterial blood partial pressure of CO2 of above 40 mmHg and is a feature of chronic lung disease. In previous studies we have demonstrated that hypercapnia modulates agonist‐stimulated cAMP levels through effects on transmembrane adenylyl cyclase activity. In the airways, cAMP is known to regulate cystic fibrosis transmembrane conductance regulator (CFTR)‐mediated anion and fluid secretion, which contributes to airway surface liquid homeostasis. The aim of the current work was to investigate if hypercapnia could modulate cAMP‐regulated ion and fluid transport in human airway epithelial cells. We found that acute exposure to hypercapnia significantly reduced forskolin‐stimulated elevations in intracellular cAMP as well as both adenosine‐ and forskolin‐stimulated increases in CFTR‐dependent transepithelial short‐circuit current, in polarised cultures of Calu‐3 human airway cells. This CO2 ‐induced reduction in anion secretion was not due to a decrease in HCO3 − transport given that neither a change in CFTR‐dependent HCO3 − efflux nor Na + /HCO3 − cotransporter‐dependent HCO3 − influx were CO2 ‐sensitive. Hypercapnia also reduced the volume of forskolin‐stimulated fluid secretion over 24 h, yet had no effect on the HCO3 − content of the secreted fluid. Our data reveal that hypercapnia reduces CFTR‐dependent, electrogenic Cl − and fluid secretion, but not CFTR‐dependent HCO3 − secretion, which highlights a differential sensitivity of Cl − and HCO3 − transporters to raised CO2 in Calu‐3 cells. Hypercapnia also reduced forskolin‐stimulated CFTR‐dependent anion secretion in primary human airway epithelia. Based on current models of airways biology, a reduction in fluid secretion, associated with hypercapnia, would be predicted to have important consequences for airways hydration and the innate defence mechanisms of the lungs. Key points: Raised arterial blood CO2 (hypercapnia) is a feature of many lung diseases. CO2 has been shown to act as a cell signalling molecule in human cells, notably by influencing the levels of cell signalling second messengers: cAMP and Ca 2+ . Hypercapnia reduced cAMP‐stimulated cystic fibrosis transmembrane conductance regulator‐dependent anion and fluid transport in Calu‐3 cells and primary human airway epithelia but did not affect cAMP‐regulated HCO3 − transport via pendrin or Na + /HCO3 − cotransporters. These results further support the role of CO2 as a cell signalling molecule and suggests CO2 ‐induced reductions in airway anion and fluid transport may impair innate defence mechanisms of the lungs.